DEVELOPMENT OF PROBLEM – BASED LEARNING E – MODUL ON ADJUSTMENT JOURNAL MATERIAL IN VOCATIONAL HIGH SCHOOL STUDENTS - Balqis Syathiri (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2024)
The problem background of this research is the need forquality teaching materials and able to provide an understanding of adjustment journals in class X accounting. So that researchers develop E-based modules based on problem-based learning that have material suitability, attractiveness, ease of operation, and provide benefits that can make it easier for students to learn practically and effectively. There are 4 methods used in developing this e-module, namely identification, design, development, and dissemination. The instruments used are e-module validation sheets, student response questionnaires. The results showed an e-module validation questionnaire analysis developed from media experts of 4.5; Material experts at 4.6 and learning practitioners at 4.4, all three of which fall into the